2006
DOI: 10.1007/s00508-006-0688-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous dissemination in early Lyme disease

Abstract: Hematogenous dissemination has long been considered an important pathogenetic event in Lyme borreliosis but has been hard to document and characterize due to insensitive blood culture methods. In a series of recent investigations involving adult patients from the United States with erythema migrans, it was concluded that plasma was a better source of culture material than serum or whole blood, and yield correlated directly with the volume of material cultured. The rate of recovery of Borrelia burgdorferi from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…A recent study of patients with EM showed a greater recovery of B. burgdorferi sensu stricto from blood of symptomatic patients; nevertheless, the majority of symptomatic patients had negative blood cultures (371), raising doubts about the reliability of the assumption that the presence of symptoms indicates dissemination.…”
Section: Laboratory Diagnosismentioning
confidence: 97%
“…A recent study of patients with EM showed a greater recovery of B. burgdorferi sensu stricto from blood of symptomatic patients; nevertheless, the majority of symptomatic patients had negative blood cultures (371), raising doubts about the reliability of the assumption that the presence of symptoms indicates dissemination.…”
Section: Laboratory Diagnosismentioning
confidence: 97%
“…With the genetic disruption or absence of these adhesins, spirochetes may be unable to travel by conventional routes or access important microenvironmental niches and thus manifest their altered dissemination phenotype. Although the extracellular matrix (ECM) is important in B. burgdorferi dissemination, as evidenced by direct dissemination through connective tissue (26,27,28,29), spirochetes utilize alternate means to disseminate as well, including bacteremia (19,29,30,31). In addition, a relatively unexplored means of dissemination is through lymphatics, as draining lymph nodes are often culture positive sooner than any other tissues proximal to the inoculation site (20,25,32).…”
mentioning
confidence: 99%
“…In Danish Ixodes ricinus three different genospecies were simultaneously present in at least 40% of the ticks (32). Borrelia sensu stricto was found in blood plasma from nearly half of the erythema migrans of American patients when large volumes of blood plasma were used as source of spirochete cultivation (33). Lyme borreliosis, with incidence that has increased in northern countries, becomes chronic and variable.…”
mentioning
confidence: 99%